Factors Affecting Land And Building Tax And Locally-Generated Revenue Kutai Timur District - Akbar Lufi Zulfikar; Swadia Gandhi Mahardika (International Journal of Economics and Management Research, 2023)
The purpose of this study is to analyze PDRB per capita and the number of taxpayers that affect land and building taxes and locally-generated revenue. This research is causality research, which analyzes the effect of exogenous variables on endogenous variables. The variables used are PDRB Per Capita, Number of Taxpayers, Land Building Tax and Regional Original Income in East Kutai Regency. The data used in this study are secondary time series data from 2011 to 2020 sourced from the Regional Revenue Service of East Kutai Regency and the Central Statistics Agency (BPS) of East Kutai Regency, using Path Analysis.The results of the per capita GDP research have a positive and significant effect on the Building Land Tax, Taxpayers have a negative and insignificant effect on the Building Land Tax. Then PDRB Per capita has a positive and significant effect, Taxpayers have a negative and insignificant effect on Regional Original Income. Land and Building Tax has a significant effect on Regional Original Income. The indirect effect of Per capita PDRB has a negative and insignificant effect on Regional Original Income through the Land and Building Tax. The indirect effect of the Taxpayer has a positive and insignificant effect on Regional Original Income through the Land and Building Tax in East Kutai Regency.